Mechanical properties and dry sliding wear behaviour of Al–Si–Mg alloy by equal channel angular pressing - Nur Farah Bazilah Wakhi Anuar; Mohd Shukor Salleh; Mohd Zaidi Omar; Saifudin Hafiz Yahaya (AIMS Materials Science, 2022)
This study investigated the microstructure, hardness, tensile and tribological behaviour of a cooling slope Al–Si–Mg alloy following ECAP and T6 heat treatment. The optical and scanning electron microscopes were applied to investigate the microstructure of the as-cast material and heat-treated ECAPed Al–Si–Mg alloy. The dry sliding wear test was tested with three different loads of 10 N, 50 N, and 100 N with constant sliding speed and sliding distance at 1.0 m/s and 9000 m, respectively, using the pin-on-disc tribometer. The hardness and tensile properties were evaluated through microhardness, UTS, and YS measurement for the as-cast Al–Si–Mg alloy, both heat-treated with and without ECAPed alloys. Moreover, wear rate and COF in the Al–Si–Mg alloy with different loads were analysed and linked with microstructural and strength behaviour after the ECAP process. Meanwhile, these analyses of results were correlated with the behaviour of the as-cast Al–Si–Mg aluminium alloy and heat-treated non-ECAPed alloy. Results demonstrated that a combination of ECAP processing and T6 heat treatment improves the mechanical behaviour, while the COF and wear rate are improved at a load of 100 N.